On decoloniality : concepts, analytics, praxis - Mignolo, Walter; Walsh, Catherine E. (On decoloniality., 2018)
Walter D. Mignolo and Catherine E. Walsh introduce the concept of decoloniality by providing a theoretical overview and discussing concrete examples of decolonial projects in action.